ChemInform Abstract: Highly Enantioselective Transfer Hydrogenation of Ketones with Chiral (NH)2P2 Macrocyclic Iron(II) Complexes. Issue 34 (August 2015) - Bigler, Raphael; Huber, Raffael; Mezzetti, Antonio
Abstract Several iron complexes are presented with the pictured compound FEC being one of the most promising catalysts for the title reaction.